TEMPERATURE CHARACTERISTICS OF A THIN AND COMPACT LINEAR SWITCHED RELUCTANCE MOTOR - Maslan, M.N.; Sato, K. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
This study describes the temperature characteristics of a thin and compact linear switch reluctance motor (LSRM). The motor does not include bulky permanent magnets, resulting a thin and compact basic structure. However, it is important to examine the temperature characteristics of the LSRM due to temperature changes are considered as an undesirable condition in high-precision systems. Although various precision positioning and tracking experiments were carried out, the characteristics of temperature rise at the time of driving remains unclear. In order to know the extent of the temperature rise, the temperature of the stator coils by the motion control system was measured experimentally using thermography. Three experimental cases were conducted depending on the input signal. It is found that continuous motion longer than 30 s increases the temperature of the LSRM only by less than 3 °C. The experimental results indicate and highlight the key advantage of LSRMs that have less thermal problems compared with permanent magnet linear motors.